Atrofia nieformalnej diagnostyki edukacyjnej we wczesnej edukacji. Między biernością i przemocą poznawczą w epoce ekspertów - Grażyna Szyling (Problemy Wczesnej Edukacji)
In the paper I present results of studies recognising the place of informal educational diagnostics in early school education. I have subjected to analysis observations of lessons placed in 85 student portfolios, treating them as data found. For the coding and categorisation of data I have used the theory of technologically-oriented educational diagnostics. The results obtained revealed spheres of substantial desistance in informal teacher diagnosing, which creates conditions favouring occurrence of symbolic violence against pupils. The decline of teachers’ diagnostic abilities, as the source of this situation, I associate with the meaning which is commonly assigned to educational (curricular) packages offered by publishing houses, the quality of which has not been confirmed empirically in the process of trial implementations or standardisation, and which, despite that, are regarded as products of experts.